Structural Performance of Reinforced Concrete Beams Subjected to Service Loads Coupled with Corrosion of Flexural Reinforcement - Al-Bayti, Abdullah (Université d'Ottawa / University of Ottawa, 2022)
Corrosion of steel reinforcement has been identified as one of the major problems facing many existing reinforced concrete structures including bridges. The exposure to aggressive environmental conditions such as those with high concentrations of chloride ions due to the use of de-icing salt in cold regions or high concentrations of carbon dioxide due to increased greenhouse gas emissions, accelerate the initiation process of corrosion. As corrosion initiates, the structural performance in terms of load-carrying capacity, ductility, and service life deteriorate over time. Coupling the effect of reinforcement corrosion with service loads may further weaken the structural performance of reinforced concrete bridges due to the presence of transverse load-induced cracks. Accordingly, a research program was conducted to evaluate the structural performance of reinforced concrete beams subjected to coupled effects of service loads and reinforcement corrosion. The research project consisted of combined experimental and numerical investigations. The experimental phase consisted of tests of nine small-scale beams and six large-scale beams. The beams were designed, constructed, instrumented, and loaded under a four-point load test. The primary test variables were the applied corrosion current density, level of corrosion, and level of sustained loading as percentage of beam ultimate capacity (0% Pu, 40% Pu, and 60% Pu). The corrosion level of steel reinforcement was quantitatively assessed using gravimetric weight measurements and three-dimensional laser scanner technique. Test results indicated that failure of corroded RC beams was brittle due to premature rupture of corroded steel bars, which was attributed to the development of localized corrosion at the sections with flexural cracks in beams. Furthermore, it was found that beams subjected to higher levels of service loads, experienced further reductions in ultimate load capacity and ductility. In addition, tensile tests were used to evaluate the effect of corrosion on the mechanical performance of steel bars retrieved from the corroded beams. It was found that the tensile strength of corroded steel bars, based on nominal sectional area, was reduced with the increase of corrosion levels. In contrast, the tensile strength, based on minimum sectional area, was not influenced by the non-uniform distribution and localization of corrosion. In fact, there was a slight increase in strength with the increase of corrosion levels. The numerical phase consisted of finite element analyses of beams using DIANA FE analysis software. A simplified approach was implemented to introduce the damage induced by corrosion into two-dimensional nonlinear FE models, based on the experimental testing of corroded beams and corroded steel bars. The analyses were reasonably accurate in predicting cracking patterns, residual load capacity, residual ductility, and failure modes of corroded beams. Subsequently, the validated model was used to conduct a parametric study on the level of service loads, level of corrosion, strength of concrete, and tensile reinforcement ratio. It was found that the FE model of corroded beams was strongly influenced by the level of service loads, level of corrosion, and tensile reinforcement ratio.
Keywords: Structural behavior; Reinforced concrete beams; Reinforcement corrosion; Service loads; Experimental investigation; Four-point bending test; Sustained loading; Corroded steel bars; Laser scanner; Direct tensile test; Finite element analysis